2020
DOI: 10.46900/apn.v2i3(september-december).44
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus and Dandy- Walker Malformation: a review

Abstract: Introduction: Dandy Walker malformation (DWM) is characterized by agenesis or hypoplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle leading to an increase of the posterior fossa and superior dislocation of the lateral sinus, tentorium and torcula. Although it is the commonest posterior fossa malformation, its pathogenesis is still not fully understood, making the differential diagnosis with other posterior fossa malformations difficult and as a result the choice of therapeutic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Prenatal regular sonography throughout the antenatal period has helped some obstetricians discover this malformation [14] . According to 7 different studies following prenatal ultrasonographic examinations, 80% of individuals with DWM showed no signs of hydrocephalus, suggesting that hydrocephalus may develop during the neonatal period [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal regular sonography throughout the antenatal period has helped some obstetricians discover this malformation [14] . According to 7 different studies following prenatal ultrasonographic examinations, 80% of individuals with DWM showed no signs of hydrocephalus, suggesting that hydrocephalus may develop during the neonatal period [15] .…”
Section: Discussionmentioning
confidence: 99%